Percutaneous mitral valve repair in adults with congenital heart disease: Report of the first case‐series. Issue 3 (8th September 2020) - Alshawabkeh, Laith; Mahmud, Ehtisham; Reeves, Ryan
Abstract: Background: Systemic atrioventricular valve regurgitation (AVVR) is frequently encountered in adults with congenital heart disease (CHD). Surgical intervention is the mainstay of therapy, but in a specific high‐risk subset, percutaneous valve repair might offer a lower‐risk alternative. Methods: Three patients with complex CHD and severe symptomatic AVVR underwent percutaneous mitral valve repair at a single center. All were deemed to be high‐risk for surgery by a multidisciplinary CHD team and provided informed consent for the compassionate use of the MitraClip (Abbott, Santa Clara, CA). Three‐dimensional heart models were generated for the procedure, which was performed by an adult CHD cardiologist (who provided imaging support) and an interventional cardiologist with expertise in CHD and percutaneous mitral valve repair. Results: The first case was a 39 year‐old‐woman with [S, L, D] dextrocardia, double outlet right ventricle, mild tricuspid hypoplasia, and a secundum atrial septal defect, who was palliated at age 35 with a right bidirectional Glenn and later developed severe, symptomatic mitral regurgitation, and underwent placement of one MitraClip XTR device. Two patients with L‐loop transposition of the great arteries each successfully underwent placement of two MitraClip XTR devices; one patient had a single‐leaflet detachment of one of the clips with no change in regurgitation or clip position on follow‐up. All patients had significant reduction of AVVR and improvement in NYHA functional class. Conclusions: Percutaneous atrioventricular valve repair in adults with CHD is feasible with the MitraClip but requires significant preprocedural planning and a multidisciplinary team that combines CHD and interventional therapeutic expertise.